Study of the Potential Use of Lithium in Treatment of Acute Kidney Injury in Rat Model - Kora, Mahmoud Abdelaziz; Yassin, Yassin Salah; Zahran, Ahmed Mohamed; Ragheb, Ahmed; Abdellatif, Safwa Othman; Elbatsh, Maha; Yousef, Wael Mohamed; El-Rebey, Hala Said; Mohamed, Asmaa Shams El-Dein (Journal of Nobel Medical College, 2018)
Background: Management of acute kidney injury is still facing a big problem. It is only dependent up till now on supportive measures, like fluid resuscitation and renal replacement therapy. No current drug therapy has been approved for the treatment of acute kidney injury. Acute kidney injury situations in a lot of cases can be predicted so, finding a drug for AKI will really benefit many patients. The pathophysiology of AKI is complex and many signaling pathways are involved in it. The Glycogen synthase kinase 3B enzyme is an important member in some of these pathways. The effect of its inhibition by the FDA approved drug, lithium on AKI is still under study.Material & Methods: The current study was conducted on28 Male Sprague–Dawley rats. We classified the rats into groups. We induced acute kidney injury to rats with cisplatin. We administered lithium chloride to treat AKI in comparison with saline treatment. We have done renal functions and histopathological examinations to all rats enrolled in our study.Results: Single intraperitoneal injection of cisplatin (5 mg/kg) in rat induced acute kidney injury. The effect of lithium chloride treatment with dose (80 mg/kg) on serum creatinine and blood urea levels showed significant regression in the rising of serum creatinine and blood urea in lithium chloride treated rats in comparison to saline-treated rats. Pathological pictures and scores demonstrated an improvement in lithium chloride treated rats than saline-treated but results were not significant.Conclusion:Administration of lithium may be a promising treatment for acute kidney injury.Journal of Nobel Medical CollegeVolume 6, Number 2, Issue 11 (July-December, 2017) Page:14-19